COSMECEUTICAL IMPORTANCE OF FERMENTED PLANT EXTRACTS: A SHORT REVIEW - Sivamaruthi, Bhagavathi Sundaram; Chaiyasut, Chaiyavat; Kesika, Periyanaina (International Journal of Applied Pharmaceutics, 2018)
Personal care products, especially cosmetics, are regularly used all over the world. The used cosmetics are discharged continuously into the environment that affects the ecosystem and human well-being. The chemical and synthetic active compounds in the cosmetics cause some severe allergies and unwanted side effects to the customers. Currently, many customers are aware of the product composition, and they are stringent in product selection. So, cosmetic producers are keen to search for an alternative, and natural active principles for the development and improvisation of the cosmetic products to attain many customers. Phytochemicals are known for several pharmacological and cosmeceutical applications. Fermentation process improved the quality of the active phytochemicals and also facilitates the easy absorption of them by human system. Recently, several research groups are working on the cosmeceutical importance of fermented plant extracts (FPE), particularly on anti-ageing, anti-wrinkle, and whitening property of FPE. The current manuscript is presenting a brief on cosmeceutical importance of FPE. <!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <span style="font-size: 12.0pt; mso-bidi-font-size: 18.0pt; line-height: 107%; font-family: 'Cambria','serif'; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;" lang="EN-US">COSMECEUTICAL IMPORTANCE OF FERMENTED PLANT EXTRACTS: A SHORT REVIEW